Culturo-Techno-Contextual Pedagogy for Biological Diversity: Implementing the Flipped Classroom Tri Kaya Parisudha Model to Foster Gender-Inclusive Critical Thinking - Indrawan, I Putu Oktap; Mahanal, Susriyati; Rohman , Fatchur; Gofur , Abdul (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
This study aims to explore the effectiveness of flipped classroom innovations through the implementation of a culturo-techno-contextual approach, specifically focusing on enhancing critical thinking skills among biology students while considering gender differences. Critical thinking is recognised as a vital competency for 21st-century learners to analyse, evaluate, and synthesise information for informed decision-making. The research methodology employed in this study is a Concurrent Embedded Design. The quantitative aspect involves a quasi-experimental design, wherein a sample of 295 secondary school biology students is divided into an experimental group, which engages with the culturo-techno-contextual flipped classroom model, two positive control groups, and one negative control group. The qualitative component encompasses the results of observations, the completion of worksheets, and reflective learning experiences from both students and teachers. Quantitative data were analysed using two-way ANCOVA, while qualitative data were analysed descriptively. The results showed that the experimental group significantly outperformed the control group in critical thinking assessment. Furthermore, gender analysis showed that both male and female students benefited from the cultural-techno-contextual approach, with female students showing higher improvements in critical thinking skills compared to male students. This study contributes to the existing literature by demonstrating the efficacy of a culturo-techno-contextual flipped classroom model in enhancing critical thinking skills, while also addressing the importance of gender considerations in educational outcomes. The findings underscore the potential of innovative pedagogical strategies to create inclusive learning environments that foster critical thinking across diverse student populations.